Carbonyl Reduction of Flubendazole in the Human Liver: Strict Stereospecificity, Sex Difference, Low Risk of Drug Interactions - Kubíček, Vladimír; Skálová, Lenka; Skarka, Adam; Králová, Věra; Holubová, Jana; Štěpánková, Jana; Šubrt, Zdeněk; Szotáková, Barbora (Frontiers in Pharmacology, 2019)
Flubendazole (FLU), an anthelmintic drug of benzimidazole type, is now considered a promising anti‐cancer agent due to its tubulin binding ability and low system toxicity. The present study was aimed at determining more information about FLU reduction in human liver, as this information has been insufficient until now. Subcellular fractions from the liver of 12 human patients (6 males and 6 females) were used to study the stereospecificity, cellular localization, coenzyme preference, enzyme kinetics and possible inter-individual or sex differences in FLU reduction. In addition, the risk of FLU interaction with other drugs was evaluated. Our study showed that FLU is predominantly reduced in cytosol and the NADPH coenzyme is preferred. The strict stereospecificity of FLU carbonyl reduction was proven and carbonyl reductase 1 was identified as the main enzyme of FLU reduction in the human liver. A higher reduction of FLU and a higher level of carbonyl reductase 1 protein was found in males than in females, but overall inter-individual variability was relatively low. Hepatic intrinsic clearance of FLU is very low and FLU had no effect on doxorubicin carbonyl reduction in the liver and in cancer cells. All these results fill the gaps in the knowledge of FLU metabolism in human.